Preliminary Study on Kecalok, An Indigenous Shrimp Sauce from Indonesia - Mahrus Ali; Ardiansyah Kurniawan; Nuning Mahmudah Noor (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2019)
Kecalokis recognized as a typical shrimp sauce traditionally produced by the Malay inhabitants in Bangka Island and Palembang, Southern region of Sumatra. Comparing to terasi, the most common Indonesian fermented shrimp, the information on kecalokhas rarely been reported. This study aimed to obtain the characteristics of both the geographical origin of kecalokproduct from Bangka and Palembang. A descriptive analysis was used to observe the profiles of both kecalokproducts including sensory, microbiology, proximate, and physical analysis. Results showed that kecalokfrom both locations had similar characteristics, i.e. a distinctive taste and aroma, high nutrition value, and containing some useful bacteria (LAB) which have beneficial role in human body. Therefore, kecalokwill be a prospective functional based-indigenous food in Indonesia.